A world without why - Geuss, Raymond (Princeton University Press, 2014)
Wishful thinking is a deeply ingrained human trait that has had a long-term distorting effect on ethical thinking. Many influential ethical views depend on the optimistic assumption that, despite appearances to the contrary, the human and natural world in which we live could, eventually, be made to make sense to us. In A World without Why, Raymond Geuss challenges this assumption. The essays in this collection--several of which are published here for the first time--explore the genesis and historical development of this optimistic configuration in ethical thought and the ways in which it ha.